An Alternate Diagnostic Algorithm for the Diagnosis of Intraepithelial Fallopian Tube Lesions - Perrone, Marie E; Reder, Nicholas P; Agoff, Sergay N; Garcia, Rochelle L; Agnew, Kathy J; Norquist, Barbara M; Pennington, Kathryn P; Swisher, Elizabeth M; Kilgore, Mark R (International journal of gynecological pathology, 2020)
Intraepithelial fallopian tube neoplasia is thought to be a precursor lesion to high-grade serous carcinoma of the Müllerian adnexae, particularly in women with BRCA1 or BRCA2 mutations. This association has led to recommendations to assess fallopian tubes for intraepithelial atypia. However, the diagnostic reproducibility of a diagnosis of intraepithelial neoplasia is unclear. In this study, 2 gynecologic pathologists independently evaluated sections of fallopian tubes from a sample of women (N=198, 623 slides) undergoing salpingectomy. A total of 101 (54%) women were undergoing risk-reducing salpingo-oophorectomy. Pathologists were blinded to patient histories and prior diagnoses. Pathologists rendered one of three diagnoses for each slide: "negative for fallopian tube intraepithelial neoplasia (FTIN)," "indeterminate for FTIN," or "definite for FTIN." Cases that were considered by histology definite for FTIN or suspicious for FTIN were stained with p53 and Ki67. Pathologists agreed on the diagnosis of "definite for FTIN" 61.5% of the time. There was no agreement on any cases for the diagnosis of "indeterminate for FTIN." Fifteen "indeterminate for FTIN" and 12 "definite for FTIN" cases were stained with p53 and Ki67. Two of the "indeterminate" cases (13%) had p53-positive foci. Five of the "definite" cases had p53-positive foci. In 3 of the other 8 "definite" cases, there was obvious carcinoma present, but the carcinoma did not stain with p53, suggesting a possible null phenotype. We propose that immunostains should only be used to aid in the diagnosis of FTIN in cases with indeterminate histology. The use of p53 immunohistochemistry in cases that were considered "definite for FTIN" by histology was minimally helpful, and in fact often served to further confuse the diagnosis.